Carbon-coated lithium iron phosphate active material and preparation method thereof, positive pole piece and lithium battery
By regulating the carbon cladding structure of carbon-coated lithium iron phosphate material, using electrostatic spray gun technology and crosslinking agent solution to form a uniform conductive network, the problem of discomfort in carbon cladding thickness is solved and the electrochemical performance of lithium-ion batteries is improved and cycle stability.
Patent Information
- Application Number
- CN202411719692.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-27
AI Technical Summary
The existing carbon-coated lithium iron phosphate (LiFePO4) materials have low electrical conductivity, and the unsuitable thickness of the carbon-coated layer leads to a decrease in the lithium ion transmission rate and energy density, and high-temperature calcination leads to excessive particles affecting electrical performance.
By controlling the range of carbon coating factor β (0.80g/cm2-22.00g/cm2), the carbon coating structure of carbon-coated lithium iron phosphate active material is regulated to ensure the ratio and uniformity of graphitized carbon and amorphous carbon. , a uniform conductive network is formed by combining electrostatic spray gun technology and crosslinking agent solution.
It improves the electrochemical performance of lithium-ion batteries, reduces the internal resistance growth rate and charge transfer impedance, and improves the cycle capacity retention rate and overall battery performance.
Smart Images

Figure CN119208580A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a carbon-coated lithium iron phosphate active material and a preparation method thereof, a positive electrode sheet and a lithium battery. Background Art
[0002] As a cathode material for lithium-ion batteries, lithium iron phosphate (LiFePO4) not only has the advantages of high energy density, high operating voltage, environmental friendliness and no memory effect, but its unique olivine structure makes LiFePO4's cycle performance and safety performance better than similar cathode materials. However, this olivine structure cannot form a continuous FeO6 conductive network, resulting in low conductivity of LiFePO4.
[0003] To this end, many researchers have proposed various solutions to this problem, such as carbon coating, metal ion doping and material nano-materials. The commonly used and industrially used method is carbon coating, that is, preparing a carbon coating layer on the outside of LiFePO4 to become LiFePO4 / C to improve the conductivity of its material. However, this method still has shortcomings. For example, if the carbon coating layer is too thick, the lithium ion transmission channel will become longer, affecting the lithium ion transmission rate, and reducing the tap density of LiFePO4 / C, thereby reducing the energy density; if the carbon coating layer is too thin, it is easy to be incompletely coated, and the conductive network fails to completely cover LiFePO4, affecting the electron transmission rate. At the same time, the carbon in the carbon coating layer usually exists in the form of amorphous carbon and graphitized carbon. Graphitized carbon has higher conductivity, but it often requires longer time and higher calcination temperature. However, long-term high calcination temperature causes LiFePO4 to grow excessively and the particle size is too large, affecting the overall electrical properties of lithium iron phosphate.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon-coated lithium iron phosphate active material and a preparation method, a positive electrode plate and a lithium battery, aiming to provide a carbon-coated lithium iron phosphate active material with low impedance and excellent cycle performance to improve the electrochemical performance of lithium batteries.
[0006] The present invention is achieved in that: In a first aspect, the present invention provides a carbon-coated lithium iron phosphate active material, comprising a lithium iron phosphate matrix and a carbon coating layer coated on the lithium iron phosphate matrix; The carbon coating factor β of carbon-coated lithium iron phosphate active material is 0.80 g / cm 2 -22.00g / cm 2 ; The expression of carbon coating factor β is: ; In the formula, IG represents the peak intensity of graphitized carbon G bond in the Raman spectrum of carbon-coated lithium iron phosphate active material; I D represents the peak intensity of amorphous carbon D bonds in the Raman spectrum of carbon-coated lithium iron phosphate active materials; A represents the carbon content per unit mass of carbon-coated lithium iron phosphate active material, in g / g; S LFP / C Represents the specific surface area of carbon-coated lithium iron phosphate active material, in cm 2 / g; represents the uniformity coefficient; The expression of uniformity coefficient ; in, It represents the peak intensity of amorphous carbon D bond in the micro-area Raman spectrum of carbon-coated lithium iron phosphate active material; It represents the peak intensity of graphitized carbon G bond in the micro-area Raman spectrum of carbon-coated lithium iron phosphate active material; The Raman spectrum of the carbon-coated lithium iron phosphate active material shows the The peak intensity of the PO bond in ; is the sample standard deviation of X, n is the number of samples tested, representing n local locations on the carbon-coated lithium iron phosphate active material; x̄ is the average value of X at each local location.
[0007] In an optional embodiment, the carbon coating factor β is 4 g / cm 2 -10g / cm 2 ; and / or, in the expression of β, The value range of is 0.2-0.8; and / or, A has a value in the range of 0.003 g / g to 0.050 g / g; and / or, S LFP / C The value range is 5cm 2 / g-20cm 2 / g; and / or, the uniformity coefficient is in the range of 3000-10000; And / or, n≥10 in the expression of uniformity coefficient.
[0008] In an optional embodiment, the general structural formula of the lithium iron phosphate matrix is Li 1-x J x Fe 1-y M y (PO4-z )Q z ; Wherein, J is selected from at least one of Na and Mg; M is at least one selected from Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; Q is selected from at least one of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1.
[0009] In a second aspect, the present invention provides a method for preparing a carbon-coated lithium iron phosphate active material according to any one of the aforementioned embodiments, to prepare a carbon-coated lithium iron phosphate active material having a carbon coating factor β that meets requirements.
[0010] In an optional embodiment, it includes: The iron phosphate, the lithium source and the carbon source are mixed and subjected to a calcination treatment to obtain a first coated lithium iron phosphate; Mixing the first coated lithium iron phosphate with the cross-linking agent solution and drying them to obtain a pretreated first coated lithium iron phosphate; Spraying the pretreated first coated lithium iron phosphate into the fluid device through a first electrostatic spray gun to form a suspended charged pretreated first coated lithium iron phosphate; The polymer solution is sprayed into the fluid device by a second electrostatic spray gun to form charged polymer droplets, which are combined with the charged pre-treated first coated lithium iron phosphate, and then a two-stage calcination treatment is performed.
[0011] In an optional embodiment, during the preparation of the first coated lithium iron phosphate, iron phosphate, a lithium source, a doping source and a carbon source are mixed to obtain a reactant, the reactant is added to a solvent and ball-milled to obtain a slurry, and the slurry is subjected to a calcination treatment in an inert atmosphere; wherein the solvent is selected from at least one of water, methanol, ethanol, acetone and dimethylformamide; and / or, in a calcination treatment process, the calcination temperature is controlled to be 450° C.-800° C., and the calcination time is controlled to be 8 h-20 h; and / or, during a calcination process, controlling the heating rate to be 2°C / min-5°C / min; and / or, the carbon source accounts for 4%-10% of the total mass of the feedstock; And / or, the carbon source comprises a first carbon source and a second carbon source, the first carbon source is selected from at least one of glucose, starch, cellulose, sucrose, citric acid, polyethylene glycol and phenolic resin; the second carbon source is selected from at least one of polyacrylonitrile and polyacrylamide; the mass ratio of the first carbon source to the second carbon source is (1-3): 1; and / or, the lithium source is selected from at least one of Li2CO3, LiH2PO4 and Li3PO4; And / or, the doping source includes at least one of a metal doping source and a non-metal doping source; the metal doping source includes at least one of a J source and an M source; wherein the J source contains at least one of Na and Mg elements, and the M source contains at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y elements; the J source is selected from at least one of oxides, hydroxides, nitrates and organic acid salts; the M source is selected from at least one of oxides, hydroxides, nitrates and organic acid salts. The non-metal doping source is a Q source, the Q source contains at least one of F, S, N and Cl elements, and the Q source is selected from at least one of metal compounds and organic salts.
[0012] In an optional embodiment, the fluid device is a device for dynamically suspending the charged pretreated first coated lithium iron phosphate using an airflow; and / or, the electrostatic voltage of the first electrostatic spray gun is 30 kV-50 kV, and the electrostatic current is 10 μA-40 μA; and / or, the electrostatic voltage of the second electrostatic spray gun is 5 kV-40 kV, and the electrostatic current is 5 μA-30 μA; And / or, the second electrostatic spray gun imparts an opposite charge to the sprayed material as that of the first electrostatic spray gun.
[0013] In an optional embodiment, the crosslinking agent in the crosslinking agent solution is selected from at least one of a polyisocyanate compound and a polyepoxy compound; the polyisocyanate compound includes hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate and isophorone diisocyanate; the polyepoxy compound includes glycidyl ether, 1,3-diglycidyl ether glycerol, diglycidyl ether and ethylene glycol diglycidyl ether; and / or, the polymer in the polymer solution is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyethyleneimine, chitosan and hyaluronic acid; and / or, the concentration of the polymer solution is 0.5wt%-5.0wt%; and / or, the mass ratio of the first coated lithium iron phosphate to the polymer and the cross-linking agent is 100:(0.3-2.0):(0.001-0.200); And / or, during the second stage calcination treatment, the calcination temperature is controlled to be 500°C-800°C, and the calcination time is 1.5h-4.0h; And / or, during the second-stage calcination process, the heating rate is controlled to be 2°C / min-4°C / min.
[0014] In a third aspect, the present invention provides a positive electrode plate, comprising the carbon-coated lithium iron phosphate active material of any one of the aforementioned embodiments or the carbon-coated lithium iron phosphate active material prepared by any one of the preparation methods of the aforementioned embodiments.
[0015] In a fourth aspect, the present invention provides a lithium battery comprising the positive electrode sheet of the aforementioned embodiment.
[0016] The present invention has the following beneficial effects: the present invention comprehensively evaluates the structure of the carbon coating layer of the carbon-coated lithium iron phosphate active material through the carbon coating factor β. The amount of graphitized carbon per unit surface area of the carbon-coated lithium iron phosphate active material can be evaluated. Compared with amorphous carbon, graphitized carbon has better conductivity and can improve the conductivity of the lithium iron phosphate matrix. By regulating the carbon coating layer structure of the carbon-coated lithium iron phosphate active material, the carbon coating factor β satisfies a specific value range, which is beneficial to improve the uniform conductivity of the carbon-coated lithium iron phosphate active material, so that the internal resistance growth rate, charge transfer impedance Rct sample standard deviation, and Warburg coefficient 𝜎 sample standard deviation of the lithium-ion battery prepared therefrom are all small, thereby improving the overall electrical performance of the lithium-ion battery.
[0017] It should be added that, theoretically, the larger the carbon coating factor β, the more graphitized carbon per unit surface area of the carbon-coated lithium iron phosphate active material, the larger the uniformity coefficient, and the more uniform the carbon coating layer. G / I D +I G Under certain conditions, an excessively large carbon coating factor means that the carbon-coated lithium iron phosphate active material has too much carbon coating per unit surface area, resulting in an overly thick coating layer, which hinders lithium ion transmission and reduces the energy density of the battery. Therefore, if the carbon coating factor is too large or too small, excellent electrical performance cannot be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 TEM image of the carbon-coated lithium iron phosphate active material prepared in Example 1; Figure 2 TEM and EDS images of the carbon-coated lithium iron phosphate active material prepared in Example 5; (a) represents the TEM image, and (b) is the EDS image of the C element distribution of (a); Figure 3 This is a Raman spectrum of the carbon-coated lithium iron phosphate active material prepared in Example 1; Figure 4 This is a micro-area Raman test image of the carbon-coated lithium iron phosphate active material prepared in Example 1. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0021] The embodiment of the present invention provides a carbon-coated lithium iron phosphate active material, including a lithium iron phosphate substrate and a carbon coating layer coated on the lithium iron phosphate substrate. The inventor creatively uses a carbon coating factor β to comprehensively evaluate the structure of the carbon coating layer, and defines the expression of the carbon coating factor β as follows: ; In the formula, I G I represents the peak intensity of the graphitized carbon G bond in the Raman spectrum of the carbon-coated lithium iron phosphate active material, indicating the content of graphitized carbon in the carbon coating layer; D It represents the peak intensity of amorphous carbon D bond in the Raman spectrum of carbon-coated lithium iron phosphate active material, indicating the content of amorphous carbon in the carbon coating layer. A represents the carbon content per unit mass of carbon-coated lithium iron phosphate active material, in g / g, indicating the total amount of graphitized carbon and amorphous carbon in the carbon-coated lithium iron phosphate active material per unit mass. S LFP / C Represents the specific surface area of carbon-coated lithium iron phosphate active material, in cm 2 / g, the specific surface area is obtained by conventional testing methods.
[0022] therefore, represents the proportion of graphitized carbon in the carbon coating layer, Indicates the amount of graphitized carbon in the carbon-coated lithium iron phosphate active material. The amount of graphitized carbon per unit surface area of the carbon-coated lithium iron phosphate active material can be evaluated. Compared with amorphous carbon, graphitized carbon has better conductivity and can improve the conductivity of the lithium iron phosphate matrix. From this aspect alone, the more graphitized carbon per unit surface area of the carbon-coated lithium iron phosphate active material, the better its performance.
[0023] It represents the uniformity coefficient, which reflects the uniformity of the carbon coating layer of the carbon-coated lithium iron phosphate active material. is the sample standard deviation of X, n is the number of samples tested, representing n local locations on the carbon-coated lithium iron phosphate active material; x̄ is the average value of X at each local location.
[0024] The expression of uniformity coefficient ;in, It represents the peak intensity of amorphous carbon D bond in the micro-area Raman spectrum of carbon-coated lithium iron phosphate active material; It represents the peak intensity of graphitized carbon G bond in the micro-area Raman spectrum of carbon-coated lithium iron phosphate active material; The Raman spectrum of the carbon-coated lithium iron phosphate active material shows the The peak intensity of the PO bond in . , , It is the peak intensity of the Raman diffraction peak obtained by testing the local position of the carbon-coated lithium iron phosphate active material with a micro-area Raman spectrometer. The peak intensity of each peak measured at the same local position can reflect the chemical bond content of the local position. Amorphous carbon D bond and graphitized carbon The average peak intensity of the bond comprehensively reflects the relative content of the carbon bond, so X represents the content ratio of the carbon bond to the PO bond.
[0025] Since the non-uniformity of the carbon coating will cause different local locations to have different X, the sample standard deviation of X is calculated by Determine the uniformity of carbon coating. The smaller the value, the more uniform the carbon coating layer is. The closer it is to 10,000.
[0026] The carbon coating factor β of the carbon-coated lithium iron phosphate active material in the embodiment of the present invention is 0.80 g / cm 2 -22.00g / cm 2 , such as 0.80g / cm 2 , 1.00g / cm 2 、3.00g / cm 2 , 5.00g / cm 2 , 8.00g / cm 2 , 10.00g / cm 2 , 13.00g / cm 2 、15.00g / cm 2 、18.00g / cm 2 , 20.00g / cm 2 , 22.00g / cm 2 wait.
[0027] It should be noted that, in theory, the larger the carbon coating factor, the more highly conductive graphitized carbon the carbon-coated lithium iron phosphate active material contains per unit specific surface area, and the carbon coating layer is also very uniform. However, in the case of sufficiently ideal uniformity, that is, the uniformity coefficient is 1, an excessively large carbon coating factor means that the carbon-coated lithium iron phosphate active material has too much graphitized carbon coating per unit surface area. Excessive graphitized carbon coating may cause the coating layer to be too thick, hindering lithium ion transmission and reducing the energy density of the battery. Therefore, if the carbon coating factor is too large or too small, excellent electrical performance cannot be achieved.
[0028] In a preferred embodiment, the carbon coating factor β is 4 g / cm 2 -10g / cm 2 The electrical properties of the carbon-coated lithium iron phosphate active material with a carbon coating factor β within this range are further improved.
[0029] In some embodiments, in the expression of β, It represents the proportion of graphitized carbon in the carbon coating layer, and its value range is 0.2-0.8, such as 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc. The amount of graphitized carbon is preferably within the above range. Too little graphitized carbon coating is not conducive to improving the conductivity of the lithium iron phosphate matrix; too much graphitized carbon coating may cause the coating layer to be too thick, hindering the transmission of lithium ions and reducing the energy density of the battery.
[0030] In some embodiments, in the expression of β, the value range of A is 0.003g / g-0.050g / g, such as 0.003g / g, 0.005g / g, 0.010g / g, 0.020g / g, 0.030g / g, 0.040g / g, 0.050g / g, etc.
[0031] In some embodiments, in the expression of β, S LFP / C The value range is 5cm 2 / g-20cm 2 / g, such as 5cm 2 / g, 8cm 2 / g, 10cm 2 / g, 13cm 2 / g, 15cm 2 / g, 18cm 2 / g, 20cm 2 / g, etc.
[0032] In some embodiments, the uniformity coefficient is represented by The corresponding value range is 3000-10000, such as 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, etc.
[0033] Furthermore, n≥10 in the expression of the uniformity coefficient, to increase the accuracy of detection, the value of n can be 10, 15, 20, 25, 30, etc., and its upper limit is not limited.
[0034] In some embodiments, the lithium iron phosphate matrix has the general structure of Li 1-x J x Fe 1-y M y (PO 4-z )Q z ; In the formula, J is selected from at least one of Na and Mg, and J can be any one or more of the above elements; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, and M can be any one or more of the above elements; Q is selected from at least one of F, S, N and Cl, and Q can be any one or more of the above elements. The values of the subscripts x, y, and z in the general formula are as follows: 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1, x, y, and z can be equal or different, and can independently be 0.00, 0.03, 0.05, 0.08, 0.10, etc.
[0035] The embodiment of the present invention also provides a method for preparing a carbon-coated lithium iron phosphate active material, and prepares a carbon-coated lithium iron phosphate active material whose carbon coating factor β meets the requirements.
[0036] In some embodiments, the preparation method of the present invention prepares a uniformity coefficient by adjusting the mixing method, introducing a crosslinking agent and a polymer. The carbon-coated lithium iron phosphate active material is within the preferred range and contains a large amount of graphitized carbon per unit surface area. However, the preparation method of the carbon-coated lithium iron phosphate active material is not limited thereto, and other methods well known in the art can also be used for preparation.
[0037] The preparation method comprises the following steps: S1. Preparation of the first coated lithium iron phosphate The materials are prepared according to the general formula of the carbon-coated lithium iron phosphate active material, the iron phosphate, the lithium source and the carbon source are mixed and subjected to a calcination treatment to obtain the first coated lithium iron phosphate.
[0038] In some embodiments, iron phosphate, a lithium source, a doping source and a carbon source are mixed to obtain a reactant, the reactant is added to a solvent and ball-milled to obtain a slurry, the slurry is subjected to a calcination treatment under an inert atmosphere, and a wet ball-milling step is introduced to uniformly mix the raw materials. The solvent used in the ball-milling is selected from at least one of water, methanol, ethanol, acetone and dimethylformamide, and the solvent can be any one or more of the above.
[0039] In some embodiments, the lithium source is selected from at least one of Li2CO3, LiH2PO4 and Li3PO4, and the lithium source can be any one or more of the above. The doping source includes at least one of a metal doping source and a non-metal doping source, and the doping source can be added with only a metal doping source, or only a non-metal doping source, or both a metal doping source and a non-metal doping source. The metal doping source includes at least one of a J source and an M source, and can be added with only a J source, only an M source, or both a J source and an M source; the non-metal doping source includes a Q source.
[0040] Corresponding to the general formula of the carbon-coated lithium iron phosphate active material, the J source contains at least one of the elements Na and Mg, and the J source may contain any one or more of the above elements; the M source contains at least one of the elements Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, and the M source may contain any one or more of the above elements; the Q source contains at least one of the elements F, S, N and Cl, and the Q source may contain any one or more of the above elements. The J source is selected from at least one of oxides, hydroxides, nitrates and organic acid salts, the M source is selected from at least one of oxides, hydroxides, nitrates and organic acid salts, and the Q source is selected from at least one of metalates and organic salts. The types of the J source and the M source may be the same or different, and may be independently selected from any one or more of the above raw materials.
[0041] In some embodiments, the carbon source includes a first carbon source and a second carbon source, the first carbon source is selected from at least one of glucose, starch, cellulose, sucrose, citric acid, polyethylene glycol and phenolic resin, and the first carbon source can be any one or more of the above; the second carbon source is selected from at least one of polyacrylonitrile and polyacrylamide, and the second carbon source can be any one or more of the above. According to the different thermal decomposition temperatures in the combined carbon source, the first carbon source with a low thermal decomposition temperature is preferentially used as a reducing agent to promote the synthesis of the lithium iron phosphate matrix; and the second carbon source with a high thermal decomposition temperature and a long straight chain structure plays a blocking role during the growth of the lithium iron phosphate matrix, making the lithium iron phosphate matrix nano-sized. At the same time, the second carbon source is easy to graphitize and has a long straight chain structure that is not easy to stack. It will be distributed as evenly as possible on the lithium iron phosphate matrix, thereby forming a first coated lithium iron phosphate with a uniform carbon coating layer.
[0042] Furthermore, the mass ratio of the first carbon source to the second carbon source is (1-3):1, such as 1.0:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, etc., and the uniformity of carbon distribution is further improved by adjusting the mass ratio of the first carbon source to the second carbon source. The total amount of the first carbon source and the second carbon source accounts for 4%-10% of the total mass of the raw material, such as 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0043] In some embodiments, during a calcination treatment, the calcination temperature is controlled to be 450°C-800°C, such as 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.; the calcination time is 8h-20h, such as 8h, 10h, 15h, 18h, 20h, etc. During a calcination treatment, the heating rate is controlled to be 2°C / min-5°C / min, such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc.
[0044] Specifically, the type of inert atmosphere is not limited, and it may be nitrogen, argon, argon-nitrogen mixed gas, etc.
[0045] S2. Electrostatic bonding and calcination The first coated lithium iron phosphate is mixed with a cross-linking agent solution, and the cross-linking agent is better attached to the first coated lithium iron phosphate through liquid phase mixing, and the pre-treated first coated lithium iron phosphate is obtained after drying and removing the solvent. The pre-treated first coated lithium iron phosphate is sprayed into the fluid device through a first electrostatic spray gun to form a suspended charged pre-treated first coated lithium iron phosphate; the polymer solution is sprayed into the fluid device using a second electrostatic spray gun to form charged polymer droplets, which are combined with the charged pre-treated first coated lithium iron phosphate through electrostatic attraction, and then a two-stage calcination treatment is performed.
[0046] It should be noted that the first electrostatic spray gun converts the pretreated first coated lithium iron phosphate into charged pretreated first coated lithium iron phosphate with an electric charge, and the surface of the charged first coated lithium iron phosphate with a low carbon content caused by uneven distribution is suspended by airflow. The second electrostatic spray gun is used to make the polymer solution have an opposite charge to the charged pretreated first coated lithium iron phosphate, and the polymer solution is evenly dispersed by electrostatic repulsion. During spraying, the polymer solution can be sprayed from the top, and the insufficiently coated areas on the charged pretreated first coated lithium iron phosphate are tightly filled by gravity and electrostatic attraction. In the second calcination, the cross-linking agent and the polymer are first cross-linked into a network structure under heating to tightly coat the lithium iron phosphate, and further carbonized to form a uniformly distributed and highly graphitized cross-linked carbon coating layer.
[0047] In some embodiments, the fluid device is a device that uses airflow to dynamically suspend the charged pretreated first-coated lithium iron phosphate, such as a fluidized bed, a bubble bed, or a bubbling bed.
[0048] In some embodiments, the electrostatic voltage of the first electrostatic spray gun is 30 kV-50 kV, and the electrostatic current is 10 μA-40 μA; the electrostatic voltage of the second electrostatic spray gun is 5 kV-40 kV, and the electrostatic current is 5 μA-30 μA. The voltage and current of the first electrostatic spray gun and the second electrostatic spray gun are preferably within the above ranges, so that the charged polymer droplets can be better combined with the charged pre-treated first coated lithium iron phosphate.
[0049] Specifically, the electrostatic voltage of the first electrostatic spray gun can be 30kV, 35kV, 40kV, 45kV, 50kV, etc., and the electrostatic current of the first electrostatic spray gun can be 10μA, 20μA, 30μA, 40μA, etc. The electrostatic voltage of the second electrostatic spray gun can be 5kV, 10kV, 20kV, 30kV, 40kV, etc., and the electrostatic current of the first electrostatic spray gun can be 5μA, 10μA, 20μA, 30μA, etc. The first electrostatic spray gun is a spray gun device that imparts positive or negative charge to the sprayed material, and the second electrostatic spray gun imparts opposite charge to the sprayed material as the first electrostatic spray gun.
[0050] In some embodiments, the crosslinking agent in the crosslinking agent solution is selected from at least one of a polyisocyanate compound and a polyepoxy compound, and the crosslinking agent may be any one or more of the above. Among them, the polyisocyanate compound includes hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate and isophorone diisocyanate; the polyepoxy compound includes glycidyl ether, 1,3-diglycidyl ether glycerol, diglycidyl ether and ethylene glycol diglycidyl ether. The crosslinking agent may be any one or more polyisocyanate compounds, any one or more polyepoxy compounds, or a mixture of polyisocyanate compounds and polyepoxy compounds.
[0051] Specifically, the drying temperature and time are not limited as long as the solvent (such as water) can be fully removed. For example, the drying temperature may be 45° C.-75° C., and the drying time may be 10 h-20 h.
[0052] In some embodiments, the polymer in the polymer solution is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyethyleneimine, chitosan and hyaluronic acid, and the polymer can be any one or more of the above. The concentration of the polymer solution is 0.5wt%-5.0wt%, such as 0.5wt%, 1.0wt%, 2.0wt%, 3.0wt%, 4.0wt%, 5.0wt%, etc. The mass ratio of the first coated lithium iron phosphate to the polymer and the cross-linking agent is 100: (0.3-2.0): (0.001-0.200), such as 100: 0.3: 0.001, 100: 0.5: 0.010, 100: 0.8: 0.050, 100: 1.0: 0.080, 100: 1.3: 0.100, 100: 1.5: 0.150, 100: 1.8: 0.180, 100: 2.0: 0.200, etc. The amount of the polymer and the cross-linking agent is preferably within the above range, so that during the calcination process, they are cross-linked into a network structure to tightly encapsulate the lithium iron phosphate, and further carbonized to form a uniformly distributed and highly graphitized cross-linked carbon coating layer.
[0053] In some embodiments, during the two-stage calcination process, the calcination temperature is controlled to be 500°C-800°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.; the calcination time is 1.5h-4.0h, such as 1.5h, 2.0h, 3.0h, 4.0h, etc. During the two-stage calcination process, the heating rate is controlled to be 2°C / min-4°C / min, such as 2°C / min, 3°C / min, 4°C / min, etc. By adjusting the operating parameters of the two-stage calcination process, a highly graphitized cross-linked carbon coating layer is formed. Specifically, the two-stage calcination process can be carried out in a kiln, and the calcination atmosphere can be an inert atmosphere, such as nitrogen, argon, etc.
[0054] It should be added that the preparation method provided in the embodiment of the present invention forms a uniform conductive network on the lithium iron phosphate matrix, which avoids the uneven reaction degree in different regions of the active material due to uneven conductivity under the same charge and discharge conditions, resulting in the region being prone to accumulation of transition state compounds or incompletely reacted active substances, hindering the further migration of lithium ions and delaying charge transfer, increasing the polarization of the battery, aggravating the growth of internal resistance, and ultimately affecting the cycle performance of the lithium-ion battery.
[0055] The embodiment of the present invention also provides a positive electrode plate, including the carbon-coated lithium iron phosphate active material, and may also include a positive electrode current collector, a positive electrode active coating is formed on at least one surface of the positive electrode current collector, and the carbon-coated lithium iron phosphate active material is present in the positive electrode active coating as a positive electrode active material. Since the carbon-coated lithium iron phosphate active material has the advantages of uniform carbon coating, low impedance and good cycle performance, it is beneficial to improve the electrochemical performance of the positive electrode plate.
[0056] An embodiment of the present invention further provides a lithium battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, a separator, etc. to form a complete battery structure with good cycle performance.
[0057] Specifically, the specific types of the negative electrode sheet, electrolyte, and separator are not limited. During the charge and discharge process of the secondary battery, active ions are intercalated and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet.
[0058] In other embodiments, the battery may not be in the form of a secondary battery, but may be in the form of a battery module, a battery pack, etc.
[0059] The embodiment of the present invention provides a device, including the above-mentioned secondary battery, battery module or battery pack, which can be used as a power source of the device or as an energy storage unit of the device. The device can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0061] Carbon-coated lithium iron phosphate active materials of Examples 1-11 and Comparative Examples 1-7 were provided, and their carbon coating factors and related parameters were tested (as shown in Table 1), and the electrochemical performance of the battery was measured (as shown in Table 2). The specific steps are as follows: (1) Carbon content test LECO CS844 high-frequency combustion infrared sulfur-carbon detector detects the carbon content in carbon-coated lithium iron phosphate active materials. The test conditions are 18 mHz and 2.2 kw.
[0062] (2) Raman test German Burker RFS100 / S Raman spectrometer characterizes carbon-coated lithium iron phosphate active materials, with a scanning range of 100-2000cm -1 , excitation wavelength 514.5 nm, resolution 1 cm -1 . At 1330-1370 cm -1 The peak at 1570-1620 cm is the peak of amorphous carbon D bond in Raman spectrum. -1 The peak appearing at is the peak of the graphitized carbon G bond in the Raman spectrum. The test results of Example 1 are as follows Figure 3 shown.
[0063] (3) Micro-area Raman testing The TESCAN S8000G field emission scanning electron microscope and the WITEC UHTS300 ultra-high throughput Raman spectrometer were used together to characterize the Raman diffraction peaks at multiple local positions of the carbon-coated lithium iron phosphate active material. Ten local position points were punched on the test surface of the carbon-coated lithium iron phosphate active material, with each local position point spaced 10 μm apart; the scanning range was 100-2000 cm -1 , excitation wavelength 514.5 nm, resolution 1 cm -1 . At 960-1030cm -1 The peak at is the lithium iron phosphate matrix PO4 in the micro-area Raman spectrum. 3- The peak of the PO bond in the -1 The peak at 1570-1620 cm is the peak of amorphous carbon D bond in the micro-Raman spectrum. -1 The peak at is the peak of the graphitized carbon G bond in the micro-area Raman spectrum. The test results of Example 1 are as follows: Figure 4 shown.
[0064] (4) Specific surface area test The specific surface area was tested using the Quantachrome QUADRASORB EVO model with a sample mass of 1 g.
[0065] (5) Transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS) testing The microstructure and chemical elements of the carbon-coated lithium iron phosphate active material were tested using a G220 transmission electron microscope combined with energy dispersive spectroscopy (EDS) from FEI Company, USA. Figure 1 As shown, the test results of Example 5 are as follows Figure 2 shown.
[0066] (6) Local impedance test (LEIS) Princeton VersaSCAN LEIS micro-area scanning electrochemical workstation tests the impedance of multiple local positions of carbon-coated lithium iron phosphate active materials. Carbon-coated lithium iron phosphate active materials, acetylene black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 90:5:5 to form an electrode material as a working electrode, and a metal lithium sheet is used as a counter electrode. Ten local position points are punched on the test surface of the working electrode, each local position point is 0.1 mm apart, the frequency range is 10-2-105 Hz, and the scanning speed is 0.1-0.5 mV / s.
[0067] According to the local impedance test and circuit simulation diagram, the high-frequency charge transfer impedance Rct value and low-frequency lithium ion diffusion rate of multiple local positions of the carbon-coated lithium iron phosphate active material are obtained. The straight line in the low-frequency region is the Warburg impedance caused by the diffusion of lithium ions in the electrode, which can reflect the diffusion rate of lithium ions and the lithium ion diffusion coefficient D Li The calculation method is as follows:
[0068] Among them, 𝐷 Li is the lithium ion diffusion coefficient (cm 2 / s), R is the gas constant 8.314 J / mol·K, T is the Kelvin temperature (298.15 K), and L is the surface area of the electrode (cm 2 ), n is the number of electrons transferred when 1 mole of reactant participates in the reaction, F is the Faraday constant (96485.3 C / mol), and C is the bulk concentration of lithium ions (2×10 -2 mol / cm 3 ), the Warburg coefficient 𝜎 is the relationship between Z' and ω -1 / 2 The fitted slope of the straight line in the low-frequency region. When other values are constant, the Warburg coefficient 𝜎 is used to indicate the speed of lithium ion diffusion. The sample standard deviations of the high-frequency region charge transfer impedance Rct and the Warburg coefficient 𝜎 at multiple local locations of the carbon-coated lithium iron phosphate active material are calculated to determine whether the charge transfer and lithium ion diffusion are evenly distributed.
[0069] The test results of (1)-(6) are listed in Tables 1 and 2.
[0070] (7) Battery performance test The carbon-coated lithium iron phosphate active material obtained above was prepared into a button cell for lithium-ion battery electrochemical performance test. The specific steps are: the carbon-coated lithium iron phosphate active material, acetylene black and polyvinylidene fluoride are uniformly mixed in N-methylpyrrolidone at a mass ratio of 90:5:5, then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, it is pressed into a positive electrode sheet with a diameter of 12 mm in an argon glove box using a tablet press. The negative electrode is a metal lithium sheet, the electrolyte is 1M LiPF6-EC:DMC (volume ratio 1:1), and a polypropylene porous membrane is used as a diaphragm to test the electrochemical performance. The test voltage is 2.0-3.9 V, the test temperature is 25°C, and the test current density is 1C=170 mAh / g. The results are shown in Table 2 below.
[0071] Capacity retention rate ×100%.
[0072] Use IT5100 battery internal resistance meter to test the internal resistance of the button battery. The positive and negative test leads of the internal resistance meter touch the two ends of the cylindrical battery respectively, and read the value on the instrument after the voltage stabilizes to obtain the internal resistance value of the battery.
[0073] Internal resistance growth rate )×100%.
[0074] Take Example 1 as an example to illustrate the calculation process of parameters: Figure 3 It can be seen that the I of Example 1 G is 689.1, I D is 638.6, is 0.519; according to Figure 4 It can be seen that the micro-area Raman test of Example 1 exemplarily gives a set of data values, is 691.6, is 177.9, is 3.75, is 0.1126, It is 8874.
[0075] Table 1 Test results of carbon coating factors and related parameters of different embodiments and comparative examples
[0076] Table 2 Electrochemical performance test results of different embodiments and comparative examples
[0077] Combining Table 1 and Table 2, when the carbon coating factor β value is between 0.80-22.00, the carbon-coated lithium iron phosphate active material has a better carbon coating structure, and its carbon coating layer not only contains a large amount of graphitized carbon, but is also evenly distributed on the lithium iron phosphate matrix. Therefore, the carbon-coated lithium iron phosphate active material has a uniformly distributed conductive network, so that the corresponding charge transfer impedance Rct sample standard deviation and Warburg coefficient 𝜎 sample standard deviation are better than the control group as a whole, and the corresponding lithium-ion battery also has a lower internal resistance growth rate and excellent cycle capacity retention rate. Furthermore, when the carbon coating factor β value is between 4.00-10.00, the corresponding charge transfer impedance Rct sample standard deviation and Warburg coefficient 𝜎 sample standard deviation are smaller, and the corresponding lithium-ion battery has excellent comprehensive performance.
[0078] Comparing Example 4 and Example 10, the carbon content, S LFP / C The uniformity coefficient is not much different, but the It is 0.579, which is greater than 0.521 of Example 4, resulting in the carbon coating factor β value of Example 10 being 4.25, which is greater than 3.68 of Example 4, making the overall electrical performance of Example 10 better than that of Example 4.
[0079] Comparative Example 3 and Comparative Example 5, although , S LFP / C The carbon coating factor β of Example 3 is within the scope of the present invention, which means that the carbon-coated lithium iron phosphate active material has a relatively suitable and uniform graphitized carbon coating amount, and can form a uniform conductive network on the carbon-coated lithium iron phosphate active material, thereby avoiding the degradation of the cycle performance caused by excessive increase in internal polarization and internal resistance of the battery after long-term charging and discharging, thereby resulting in smaller electrical properties such as the internal resistance growth rate, the charge transfer impedance Rct sample standard deviation, and the Warburg coefficient 𝜎 sample standard deviation.
[0080] Comparative Examples 1-11 and Comparative Example 5 , S LFP / C The coefficient of uniformity is within the appropriate range, but the comparative example 5 has too high a carbon content, resulting in a carbon coating factor β value of 26.17. When the carbon content is too high, the amount of graphitized carbon in the material as a whole will also increase. In other words, although the overly thick carbon coating layer can bring excellent conductivity and complete coating of the lithium iron phosphate matrix, it will also hinder the diffusion of lithium ions. After a long period of cycling, the internal polarization and internal resistance of the battery increase too much, and the internal resistance growth rate is high.
[0081] It should be noted that the first electrostatic spray gun used in the following examples and comparative examples was purchased from Graco, model Pro-Xp; the second electrostatic spray gun was purchased from Graco, model Pro-Xp.
[0082] Example 1 This embodiment provides a carbon-coated lithium iron phosphate active material, and the preparation method includes the following steps: (1) FePO4, Li2CO3 and TiO2 were mixed in a molar ratio of 0.997:0.5:0.003, and a combined carbon source consisting of glucose and polyacrylonitrile was added to obtain a reactant. The reactant was added to a mixed solvent of water and dimethylformamide and mixed by ball milling to obtain a slurry. The slurry was calcined at 550°C for 15 h under nitrogen at a heating rate of 3°C / min, and naturally cooled, crushed and sieved to obtain a first coated LiFe 0.997 Ti 0.03 PO4.
[0083] The mass of the combined carbon source accounts for 6% of the total mass of the raw materials, the mass ratio of glucose to polyacrylonitrile is 2:1, and the mass ratio of water to dimethylformamide in the mixed solvent is 1:1.
[0084] (2) First coating LiFe 0.997 Ti 0.03 PO4 and a crosslinker solution containing hexamethylene diisocyanate were mixed and dried at 45°C for 15h to obtain a pretreated first coated LiFe 0.997 Ti 0.03 PO4. Pre-treatment of the first coating LiFe 0.997 Ti 0.03 PO4 is sprayed onto the fluidized bed into which compressed air is introduced by the first electrostatic spray gun to form a suspended charged pre-treated first coated LiFe 0.997 Ti 0.03 PO4 (positively charged). The second electrostatic spray gun is used to spray the polymer aqueous solution containing polyvinyl alcohol into the fluidized bed to form charged polymer droplets (negatively charged). 0.997 Ti 0.03 PO4 and the charged polymer droplets are electrostatically attracted to combine, and then placed in a kiln and heated to 600°C at 3°C / min in a nitrogen atmosphere and kept warm for 2 hours to obtain the carbon-coated lithium iron phosphate active material of Example 1.
[0085] The solvent of the crosslinking agent solution is acetone, the concentration of the crosslinking agent solution is 0.1wt%, and the concentration of the aqueous solution containing polyvinyl alcohol is 3wt%. 0.997 Ti 0.03 PO4: polyvinyl alcohol: hexamethylene diisocyanate = 100: 1: 0.1. The electrostatic voltage of the first electrostatic spray gun is 40 kV, and the electrostatic current is 20 μA; the electrostatic voltage of the second electrostatic spray gun is 25 kV, and the electrostatic current is 15 μA.
[0086] Example 2 This embodiment provides a carbon-coated lithium iron phosphate active material, and the preparation method includes the following steps: (1) FePO4, Li2CO3 and Co(NO3)2 were mixed in a molar ratio of 0.98:0.5:0.02, and a combined carbon source consisting of starch and polyacrylamide was added to obtain a reactant. The reactant was added to a water solvent and ball-milled to obtain a slurry. The slurry was calcined at 450°C under nitrogen for 20 h, and naturally cooled and crushed to obtain the first coated LiFe 0.98 Co 0.02 PO4.
[0087] Among them, the mass of the combined carbon source accounts for 4% of the total mass of the raw materials, and the mass ratio of starch to polyacrylamide is 1:1.
[0088] (2) First coating LiFe 0.98 Co 0.02 PO4 and a crosslinker solution containing diglycidyl ether were mixed and dried at 45°C for 15h to obtain a pretreated first coated LiFe0.98 Co 0.02 PO4. Pre-treatment of the first coating LiFe 0.98 Co 0.02 PO4 is sprayed onto the fluidized bed into which compressed air is introduced by the first electrostatic spray gun to form a suspended charged pre-treated first coated LiFe 0.98 Co 0.02 PO4 (positively charged). The second electrostatic spray gun is used to spray the polymer aqueous solution containing polyethyleneimine into the fluid device to form charged polymer droplets (negatively charged). 0.98 Co 0.02 PO4 and the charged polymer droplets are electrostatically attracted to combine, and then placed in a kiln and heated to 800°C at 4°C / min in a nitrogen atmosphere and kept warm for 1.5 hours to obtain the carbon-coated lithium iron phosphate active material of Example 2.
[0089] The solvent of the crosslinking agent solution is water, the concentration of the crosslinking agent solution is 0.1wt%, and the concentration of the aqueous solution containing polyethyleneimine is 5wt%. 0.98 Co 0.02 PO4: polyethyleneimine: diglycidyl ether = 100: 2: 0.2. The electrostatic voltage of the first electrostatic spray gun is 30 kV, and the electrostatic current is 10 μA; the electrostatic voltage of the second electrostatic spray gun is 5 kV, and the electrostatic current is 5 μA.
[0090] Example 3 This embodiment provides a carbon-coated lithium iron phosphate active material, and the preparation method includes the following steps: (1) FePO4, Li2CO3, LiF and MnCO3 were mixed in a molar ratio of 0.9:0.495:0.01:0.1, and a combined carbon source consisting of citric acid and polyacrylonitrile was added to obtain a reactant. The reactant was added to a mixed solvent of water and dimethylformamide and mixed by ball milling to obtain a slurry. The slurry was calcined at 800°C for 8 hours under nitrogen, and naturally cooled, crushed and sieved to obtain a first coated LiFe 0.9 Mn 0.1 PO 3.99 F 0.01 .
[0091] The mass of the combined carbon source accounts for 10% of the total mass of the raw materials, the mass ratio of citric acid to polyacrylonitrile is 3:1, and the mass ratio of water to dimethylformamide in the mixed solvent is 1:1.
[0092] (2) First coating LiFe 0.9 Mn 0.1 PO 3.99 F 0.01After mixing with a crosslinker solution containing toluene diisocyanate, the mixture was dried at 45°C for 15 hours to obtain a pretreated first coated LiFe 0.9 Mn 0.1 PO 3.99 F 0.01 . Pre-treatment of the first coating LiFe 0.9 Mn 0.1 PO 3.99 F 0.01 The first electrostatic spray gun is sprayed onto the fluidized bed into which compressed air is introduced to form a suspended charged pre-treated first coated LiFe 0.9 Mn 0.1 PO 3.99 F 0.01 (negatively charged). A second electrostatic spray gun is used to spray a polymer aqueous solution containing hyaluronic acid into the fluid device to form charged polymer droplets (positively charged). 0.9 Mn 0.1 PO 3.99 F 0.01 The charged polymer droplets are electrostatically attracted and combined, and then placed in a kiln and heated to 500° C. at a rate of 2° C. / min in a nitrogen atmosphere and kept warm for 4 hours to obtain the carbon-coated lithium iron phosphate active material of Example 3.
[0093] The solvent of the crosslinking agent solution is acetone, the concentration of the crosslinking agent solution is 0.1wt%, and the concentration of the aqueous solution containing hyaluronic acid is 0.5wt%. 0.9 Mn 0.1 PO 3.99 F 0.01 : hyaluronic acid: toluene diisocyanate = 100: 0.3: 0.001. The electrostatic voltage of the first electrostatic spray gun is 50 kV, and the electrostatic current is 40 μA; the electrostatic voltage of the second electrostatic spray gun is 40 kV, and the electrostatic current is 30 μA.
[0094] Example 4 This embodiment provides a carbon-coated lithium iron phosphate active material. In the preparation method step (1), the mass ratio of glucose to polyacrylonitrile is 1.5:1, and the other conditions are exactly the same as those in Example 1.
[0095] Example 5 This embodiment provides a carbon-coated lithium iron phosphate active material. In the preparation method step (1), the mass ratio of glucose to polyacrylonitrile is 2.5:1, and the other conditions are exactly the same as those in Example 1.
[0096] Example 6 This embodiment provides a carbon-coated lithium iron phosphate active material. In the preparation method step (2), the electrostatic voltage of the second electrostatic spray gun is 10 kV, and the other conditions are exactly the same as those in Example 1.
[0097] Example 7 This embodiment provides a carbon-coated lithium iron phosphate active material. In the preparation method step (2), the electrostatic voltage of the second electrostatic spray gun is 35 kV, and the other conditions are exactly the same as those in Example 1.
[0098] Example 8 This embodiment provides a carbon-coated lithium iron phosphate active material, the preparation method step (2) first coats LiFe 0.997 Ti 0.03 PO4: polyvinyl alcohol: hexamethylene diisocyanate = 100: 0.5: 0.1, and other conditions are exactly the same as those in Example 1.
[0099] Example 9 This embodiment provides a carbon-coated lithium iron phosphate active material. In the preparation method step (2), the first coating of LiFe 0.997 Ti 0.03 PO4: polyvinyl alcohol: hexamethylene diisocyanate = 100: 1.7: 0.1, and other conditions are exactly the same as those in Example 1.
[0100] Example 10 This embodiment provides a carbon-coated lithium iron phosphate active material. In the preparation method step (1), the mass of the combined carbon source accounts for 7% of the total mass of the raw materials, the mass ratio of glucose to polyacrylonitrile is 1:1, and the slurry is calcined at 700° C. for 10 h under nitrogen. Other conditions are exactly the same as in Example 1.
[0101] Embodiment 11 This embodiment provides a carbon-coated lithium iron phosphate active material, and the preparation method includes the following steps: (1) FePO4, Li2CO3 and TiO2 were mixed in a molar ratio of 0.997:0.5:0.003, and a combined carbon source of glucose and polyacrylonitrile was added to obtain a reactant. The reactant was added to a mixed solvent of water and dimethylformamide and mixed by ball milling to obtain a slurry. The slurry was calcined at 550°C under nitrogen for 15 h, and naturally cooled and crushed to obtain the first coated LiFe 0.997 Ti 0.03 PO4.
[0102] The mass of the combined carbon source accounts for 6% of the total mass of the raw materials, the mass ratio of glucose to polyacrylonitrile is 1.5:1, and the mass ratio of water to dimethylformamide in the mixed solvent is 1:1.
[0103] (2) First coating LiFe 0.997 Ti 0.03 PO4 and a crosslinker solution containing hexamethylene diisocyanate were mixed and dried at 45°C for 15h to obtain a pretreated first coated LiFe0.997 Ti 0.03 PO4. The first pre-coated LiFe 0.997 Ti 0.03 PO4 is introduced into the fluidized bed of compressed air to make it suspended, and the polymer aqueous solution containing polyvinyl alcohol is evenly sprayed on the suspended pre-treated first coated LiFe 0.997 Ti 0.03 PO4, and then placed in a kiln under a nitrogen atmosphere and heated to 700°C at a rate of 3°C / min and kept at that temperature for 3h to obtain the carbon-coated lithium iron phosphate active material of Example 11.
[0104] The solvent of the crosslinking agent solution is acetone, the concentration of the crosslinking agent solution is 0.1wt%, and the concentration of the aqueous solution containing polyvinyl alcohol is 3wt%. 0.997 Ti 0.03 PO4: polyvinyl alcohol: hexamethylene diisocyanate = 100: 1: 0.1. The ultrasonic frequency of ultrasonic spraying is 110kHz.
[0105] Comparative Example 1 This comparative example provides a carbon-coated lithium iron phosphate active material, the preparation method of which does not involve a second calcination of the carbon coating, and the specific steps are as follows: FePO4, Li2CO3 and TiO2 are mixed as raw materials in a molar ratio of 0.997:0.5:0.003, and a combined carbon source consisting of glucose and polyacrylonitrile is added to obtain a reactant. The reactant is added into a mixed solvent of water and dimethylformamide and mixed evenly by ball milling to obtain a slurry. The slurry is calcined at 550°C under nitrogen for 15 h, naturally cooled, crushed and sieved to obtain the carbon-coated lithium iron phosphate active material of Comparative Example 1.
[0106] The mass of the combined carbon source accounts for 7% of the total mass of the raw materials, the mass ratio of glucose to polyacrylonitrile is 2:1, and the mass ratio of water to dimethylformamide in the mixed solvent is 1:1.
[0107] Comparative Example 2 In this comparative example, step (2) pre-treats the first coated LiFe 0.997 Ti 0.03 PO4 was sprayed into the fluidized bed without gas flow through the first electrostatic spray gun so that it was not suspended. Other conditions were exactly the same as those in Example 1.
[0108] Comparative Example 3 In this comparative example, step (2) pre-treats the first coated LiFe 0.997 Ti 0.03 PO4 is directly added to the fluidized bed in a suspended state, and the polymer aqueous solution is directly sprayed on the suspended first coated LiFe 0.997 Ti 0.03On PO4, other conditions were exactly the same as in Example 1.
[0109] Comparative Example 4 This comparative example provides a carbon-coated lithium iron phosphate active material, which is prepared by a conventional secondary coating process, and the specific steps are as follows: (1) FePO4, Li2CO3, and TiO2 raw materials were mixed in a molar ratio of 0.997:0.5:0.003, and a combined carbon source consisting of glucose and polyacrylonitrile was added to obtain a reactant. The reactant was added to a mixed solvent of water and dimethylformamide and mixed by ball milling to obtain a slurry. The slurry was calcined at 550°C under nitrogen for 15 hours, and naturally cooled and crushed to obtain the first coated LiFe 0.997 Ti 0.03 PO4.
[0110] The mass of the combined carbon source accounts for 6% of the total mass of the raw materials, the mass ratio of glucose to polyacrylonitrile is 2:1, and the mass ratio of water to dimethylformamide in the mixed solvent is 1:1.
[0111] (2) Spraying a polymer aqueous solution containing polyvinyl alcohol onto the first coated LiFe 0.997 Ti 0.03 PO4, and then placed in a kiln under a nitrogen atmosphere and heated to 600°C at a rate of 3°C / min and kept warm for 2h to obtain the carbon-coated lithium iron phosphate active material of Comparative Example 4.
[0112] Among them, the first coating LiFe 0.997 Ti 0.03 PO4:polyvinyl alcohol=100:1.
[0113] Comparative Example 5 In step (1) of this comparative example, the mass of the combined carbon source accounts for 16% of the total mass of the raw materials, and other conditions are exactly the same as those in Example 1.
[0114] Comparative Example 6 In step (1) of this comparative example, the mass ratio of glucose to polyacrylonitrile is 0.5:1, the combined carbon source accounts for 12% of the total mass of the raw materials, and other conditions are exactly the same as those in Example 1.
[0115] Comparative Example 7 This comparative example provides a carbon-coated lithium iron phosphate active material, and the preparation method is as follows: In step (2) of this comparative example, the first coating LiFe 0.997 Ti 0.03 PO4 is directly sprayed onto the fluidized bed into which compressed air is introduced through the first electrostatic spray gun to form a suspended charged first coated LiFe 0.997 Ti 0.03PO4 (positively charged), the second electrostatic spray gun is used to spray the monomer aqueous solution containing vinyl acetate into the fluid device to form charged monomer droplets (negatively charged). 0.997 Ti 0.03 PO4 and charged monomer droplets are electrostatically attracted and combined, and placed in a solution containing the initiator azobisisobutyronitrile to initiate vinyl acetate polymerization, and then placed in a methanol solution for alcoholysis to obtain polyvinyl alcohol-coated first-coated LiFe 0.997 Ti 0.03 PO4, and finally placed in a kiln in a nitrogen atmosphere and heated to 600°C at 3°C / min for 2 hours to obtain the carbon-coated lithium iron phosphate active material of Comparative Example 7. 0.997 Ti 0.03 PO4:vinyl acetate:azobisisobutyronitrile = 100:1:0.002. Other conditions are exactly the same as those in Example 1.
[0116] From the results in Table 1, it can be seen that adjusting the reaction parameters of the preparation steps (1) and (2) can regulate the carbon coating structure of the carbon-coated lithium iron phosphate active material, and then regulate the carbon coating factor. Specifically, the amount of combined carbon source added in step (1) and the proportion of different carbon sources in the combined carbon source will affect the specific surface area and graphitized carbon content of the carbon-coated lithium iron phosphate active material. Compared with glucose and the like, polyacrylonitrile has a higher thermal decomposition temperature; when the first coated lithium iron phosphate is prepared by carbon thermal reduction, glucose preferentially decomposes as a reducing agent to participate in the reaction process, while the long straight-chain polyacrylonitrile has a spatial blocking effect, causing the first coated lithium iron phosphate to grow nanosized, thereby shortening the lithium ion transmission channel of the carbon-coated lithium iron phosphate active material and making it easier to diffuse. The larger the specific surface area, the easier it is to fully contact with the electrolyte.
[0117] The long straight chain structure of polyacrylonitrile makes it difficult to stack and can be evenly distributed on the first coated lithium iron phosphate. The higher the proportion of polyacrylonitrile in the combined carbon source, the more graphitized carbon is formed after the two calcinations. But similarly, because of its spatial barrier effect, the higher the proportion of polyacrylonitrile in the combined carbon source, the smaller the carbon-coated lithium iron phosphate active material particles. The larger the specific surface area of carbon-coated lithium iron phosphate active materials with the same amount of graphitized carbon, the less the amount of graphitized carbon distributed per unit surface area, and the surface conductivity may be insufficient, so and Only by matching them can excellent electrochemical performance be achieved.
[0118] In step (2), the pre-treated first coated lithium iron phosphate is made into suspended charged pre-treated first coated lithium iron phosphate by electrostatic spraying and airflow, and the surface with less and uneven carbon content distribution will face upward, and the polymer solution is evenly dispersed by electrostatic spraying and other methods to fill the surface with less and uneven carbon content distribution of the charged pre-treated first coated lithium iron phosphate, thereby forming a uniform carbon coating layer under calcination. Therefore, the Raman test results of multiple local positions on the carbon-coated lithium iron phosphate active material are X= The smaller the sample standard deviation, the greater the uniformity coefficient The larger the value, the closer it is to the maximum value 1. However, when the first coated lithium iron phosphate is not dynamically suspended, or the polymer solution is not charged by the second electrostatic spray gun, an excellent carbon coating effect cannot be achieved, which in turn affects the carbon coating factor.
[0119] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbon-coated lithium iron phosphate active material, characterized in that: It comprises a lithium iron phosphate matrix and a carbon coating layer coated on the lithium iron phosphate matrix; The carbon coating factor β of the carbon-coated lithium iron phosphate active material is 0.80 g / cm 2 -22.00g / cm 2 ; The expression of the carbon coating factor β is: ; In the formula, I G represents the peak intensity of the graphitized carbon G bond in the Raman spectrum of the carbon-coated lithium iron phosphate active material; I D represents the peak intensity of the amorphous carbon D bond in the Raman spectrum of the carbon-coated lithium iron phosphate active material; A represents the carbon content per unit mass of the carbon-coated lithium iron phosphate active material, in g / g; S LFP / C represents the specific surface area of the carbon-coated lithium iron phosphate active material, in cm 2 / g; represents the uniformity coefficient; The expression of the uniformity coefficient is ; in, represents the peak intensity of amorphous carbon D bond in the micro-area Raman spectrum of the carbon-coated lithium iron phosphate active material; represents the peak intensity of the graphitized carbon G bond in the micro-area Raman spectrum of the carbon-coated lithium iron phosphate active material; The carbon-coated lithium iron phosphate active material has a lithium iron phosphate matrix in the micro-area Raman spectrum. The peak intensity of the PO bond in ; is the sample standard deviation of X, n is the number of samples tested, representing n local locations on the carbon-coated lithium iron phosphate active material; x̄ is the average value of X at each local location.
2. The carbon-coated lithium iron phosphate active material according to claim 1, characterized in that: The carbon coating factor β is 4 g / cm 2 -10g / cm 2 ; and / or, in the expression of β, The value range of is 0.2-0.8; and / or, A has a value in the range of 0.003 g / g to 0.050 g / g; and / or, S LFP / C The value range is 5cm 2 / g-20cm 2 / g; And / or, the uniformity coefficient has a value range of 3000-10000; And / or, n≥10 in the expression of the uniformity coefficient.
3. The carbon-coated lithium iron phosphate active material according to claim 1, characterized in that: The general structural formula of the lithium iron phosphate matrix is Li 1-x J x Fe 1-y M y (PO 4-z )Q z ; Wherein, J is selected from at least one of Na and Mg; M is at least one selected from Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; Q is selected from at least one of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.
1.
4. A method for preparing the carbon-coated lithium iron phosphate active material according to any one of claims 1 to 3, characterized in that: Prepare carbon-coated lithium iron phosphate active material with a carbon coating factor β that meets the requirements.
5. The preparation method according to claim 4, characterized in that: include: The iron phosphate, the lithium source and the carbon source are mixed and subjected to a calcination treatment to obtain a first coated lithium iron phosphate; Mixing the first coated lithium iron phosphate with a crosslinking agent solution and drying them to obtain a pretreated first coated lithium iron phosphate; Spraying the pretreated first coated lithium iron phosphate into the fluid device through a first electrostatic spray gun to form a suspended charged pretreated first coated lithium iron phosphate; The polymer solution is sprayed into the fluid device by a second electrostatic spray gun to form charged polymer droplets, which are combined with the charged pre-treated first coated lithium iron phosphate, and then a two-stage calcination treatment is performed.
6. The preparation method according to claim 5, characterized in that: In the process of preparing the first coated lithium iron phosphate, iron phosphate, a lithium source, a doping source and a carbon source are mixed to obtain a reactant, the reactant is added to a solvent and ball-milled to obtain a slurry, and the slurry is subjected to the first-stage calcination treatment under an inert atmosphere; wherein the solvent is at least one selected from water, methanol, ethanol, acetone and dimethylformamide; And / or, during the first calcination process, the calcination temperature is controlled to be 450° C.-800° C., and the calcination time is controlled to be 8 h-20 h; and / or, during the first calcination process, controlling the heating rate to be 2°C / min-5°C / min; and / or, the carbon source accounts for 4%-10% of the total mass of the raw material; And / or, the carbon source comprises a first carbon source and a second carbon source, the first carbon source is at least one selected from glucose, starch, cellulose, sucrose, citric acid, polyethylene glycol and phenolic resin; the second carbon source is at least one selected from polyacrylonitrile and polyacrylamide; the mass ratio of the first carbon source to the second carbon source is (1-3):1; And / or, the lithium source is selected from at least one of Li2CO3, LiH2PO4 and Li3PO4; And / or, the doping source includes at least one of a metal doping source and a non-metallic doping source; the metal doping source includes at least one of a J source and an M source; wherein the J source contains at least one of Na and Mg elements, and the M source contains at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y elements; the J source is selected from at least one of oxides, hydroxides, nitrates and organic acid salts; the M source is selected from at least one of oxides, hydroxides, nitrates and organic acid salts; the non-metallic doping source is a Q source, the Q source contains at least one of F, S, N and Cl elements, and the Q source is selected from at least one of metal oxides and organic salts.
7. The preparation method according to claim 5, characterized in that: The fluid device is a device that uses airflow to dynamically suspend the charged pre-treated first-coated lithium iron phosphate; And / or, the electrostatic voltage of the first electrostatic spray gun is 30 kV-50 kV, and the electrostatic current is 10 μA-40 μA; And / or, the electrostatic voltage of the second electrostatic spray gun is 5kV-40kV, and the electrostatic current is 5μA-30μA; And / or, the second electrostatic spray gun and the first electrostatic spray gun impart opposite charges to the sprayed material.
8. The preparation method according to claim 5, characterized in that: The crosslinking agent in the crosslinking agent solution is selected from at least one of a polyisocyanate compound and a polyepoxy compound; the polyisocyanate compound includes hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate and isophorone diisocyanate; the polyepoxy compound includes glycidyl ether, 1,3-diglycidyl ether glycerol, diglycidyl ether and ethylene glycol diglycidyl ether; and / or, the polymer in the polymer solution is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyethyleneimine, chitosan and hyaluronic acid; and / or, the concentration of the polymer solution is 0.5wt%-5.0wt%; and / or, the mass ratio of the first coated lithium iron phosphate to the polymer and the cross-linking agent is 100:(0.3-2.0):(0.001-0.200); And / or, during the second-stage calcination treatment, the calcination temperature is controlled to be 500° C.-800° C., and the calcination time is controlled to be 1.5 h-4.0 h; And / or, during the second-stage calcination process, the heating rate is controlled to be 2°C / min-4°C / min.
9. A positive electrode sheet, characterized in that: The invention comprises the carbon-coated lithium iron phosphate active material according to any one of claims 1 to 3 or the carbon-coated lithium iron phosphate active material prepared by the preparation method according to any one of claims 4 to 8.
10. A lithium battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Method for loading TiO2 photocatalyst on ferromagnetic metal thin film
CN101463470A
LiFePO4 (lithium iron phosphate) positive electrode material with specific morphology and structure and lithium secondary battery
CN102509790A
Microcapsule preparation method and microcapsule preparation device
CN114307881A
Low-temperature lithium iron phosphate composite material and preparation method thereof
CN117985677A
Positive electrode material with olivine structure, preparation method of positive electrode material and lithium ion battery
CN118099377A
Cited By
Homogeneous lithium iron phosphate material prepared by interface strengthening and application of homogeneous lithium iron phosphate material
CN120483091A
High-performance lithium iron phosphate positive electrode material and preparation method thereof
CN120622444A
High-performance lithium iron phosphate cathode material and preparation method thereof
CN120622444B
Lithium iron phosphate material realized by dual-phase coupling coating and structure regulation and control and application of lithium iron phosphate material
CN121054659A
Coating method and coating device of battery positive electrode material
CN121709564A
